2022
DOI: 10.3390/ph15020217
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine (NAC) and Its Role in Clinical Practice Management of Cystic Fibrosis (CF): A Review

Abstract: N-acetylcysteine is the acetylated form of the amino acid L-cysteine and a precursor to glutathione (GSH). It has been known for a long time as a powerful antioxidant and as an antidote for paracetamol overdose. However, other activities related to this molecule have been discovered over the years, making it a promising drug for diseases such as cystic fibrosis (CF). Its antioxidant activity plays a key role in CF airway inflammation and redox imbalance. Furthermore, this molecule appears to play an important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Some studies have successfully used NAC to demonstrate its in vitro efficacy against planktonically grown as well as biofilms of laboratory strains of bacteria (Li et al, 2020; Aiyer et al, 2021; Chlumsky et al, 2021; Tenório et al, 2021). The antibiofilm activity of NAC is attributed to different aspects such as inhibition of EPS production, bacterial adhesion inhibition, competitive inhibition of cysteine in bacteria, interaction with bacterial proteins via thiol groups, and liquification of biofilm matrix (Zhao et al, 2010; Costa et al,2017; Manoharan et al,2020; Guerini et al,2020; Guerini et al, 2022). Some reports have shown the killing efficacy of NAC is pH-mediated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have successfully used NAC to demonstrate its in vitro efficacy against planktonically grown as well as biofilms of laboratory strains of bacteria (Li et al, 2020; Aiyer et al, 2021; Chlumsky et al, 2021; Tenório et al, 2021). The antibiofilm activity of NAC is attributed to different aspects such as inhibition of EPS production, bacterial adhesion inhibition, competitive inhibition of cysteine in bacteria, interaction with bacterial proteins via thiol groups, and liquification of biofilm matrix (Zhao et al, 2010; Costa et al,2017; Manoharan et al,2020; Guerini et al,2020; Guerini et al, 2022). Some reports have shown the killing efficacy of NAC is pH-mediated.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that NAC was bactericidal against all the XDR K. pneumoniae isolates at a concentration of 10mg/mL. Furthermore, NAC could successfully eradicate in vitro biofilms of all the XDR K. pneumonia at an acceptable concentration of 100mg/mL (Olsson et al, 1988; Hughes et al, 2018; NIH U.S. National Library of Medicine 2018, Guerini et al, 2022). Safe alternatives to antibiotics are a compelling need of the hour to treat K. pneumoniae infections to improve patient outcomes.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, NAC administration affects viral infections caused, e.g., by influenza [178] or COVID-19 [179,180]. NAC has been known for a long time as a powerful antioxidant and as an antidote for paracetamol overdose [181]. It also shows beneficial outcomes after surgery.…”
Section: Antioxidants and Redox Enzymesmentioning
confidence: 99%
“…NAC has been used for a wide variety of medical applications from respiratory diseases to cancer therapy, acetaminophen toxicity and psychiatric disorders. 1,2 Its primary mode of action is through antioxidant and anti-inammatory activity. 3 Further, oral deliver is the safest and preferred delivery method.…”
Section: Introductionmentioning
confidence: 99%